If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + -2 = 31 Multiply x * x x2 + -2 = 31 Reorder the terms: -2 + x2 = 31 Solving -2 + x2 = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x2 = 31 + 2 Combine like terms: -2 + 2 = 0 0 + x2 = 31 + 2 x2 = 31 + 2 Combine like terms: 31 + 2 = 33 x2 = 33 Simplifying x2 = 33 Take the square root of each side: x = {-5.744562647, 5.744562647}
| 6n+8=6n | | 8y+8=7y-2 | | -8x-x=-16-x | | d=4.7+2.8(12) | | 15+5m=-1+3m | | -3-6v=-v-6v | | =.8(x-25) | | 2.10+12.99b=12.39 | | -9+2k=-2k+7k | | -8a+6a=-2-4a | | 8n-4=-4+8n | | 4cosx+3sinx=y | | 5(X-15)2=75 | | 2a-4+2a=-12+3a | | n+8+2n-4=7+4n-20 | | x+2(-2)=-1 | | 8(4+7n)-6n=332 | | 6=k+7 | | 5x+5-6x=-x+5 | | y-5/y=10/8 | | m-15/4-4m-4/5=2 | | 25t^2+30x+7=0 | | y-5/5=10/8 | | 4+7+5x=0 | | 6(x+7)=5(x-7)+x | | 3x+2x+10=5x+5 | | 11x^2+30x-9=0 | | 6(x-9)x=7(x-8)+2 | | 5(3a-b)-7(3b-7a)= | | 9x+7y=-70 | | 3x+2x+10=5x+1 | | 8m(m+3)=2m-5 |